(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze how healthtechs gained more visibility, influence and developed in the face of the COVID-19 pandemic. Due to the strictly scarce literature on the subject on conventional search sites, the methodology used was a digital narrative review, which consisted of checking mainly on the websites of the health technology companies themselves, with 15 articles available. The search for information about COVID-19 followed the traditional analysis on Pubmed, Scielo and websites of the Ministry of Health and the World Health Organization, with the use of Boolean operators, having as selection criteria the articles in full of the last two years (2020-2021) with 11 articles available. Startups are companies with an innovative profile that, to be successful, need to adapt and meet the demands. Healthtechs (health technologies) aim to minimize costs and assist in a continuous and consistent manner in the formation of the market in this area. In Brazil there are currently 542 startups on new technologies and innovation in health, thus becoming the third largest sector in the industry. The pandemic has accelerated the development of healthtechs and the continued growth of these companies will move and expand the health and technology sector.